Determinan Komunikasi Sebagai Variabel Moderasi Antara Motivasi, Budaya Organisasi, dan Kepemimpinan Terhadap Kinerja Mitra PT Kangzen Kenko Indonesia Cabang Jember - Maulana, Adinda Agung; Titisari, Purnamie; Mirzania, Alif; Apriono, Markus; Sudarsih (Study Program of Management Faculty of Economics and Business University of Jember, 2025)
Human resources (HR) are an important element in any scope, whether organizational, private, government and others. The roles and functions of human resources equally support the progress of the organization and the company that houses it. This research was motivated by the concern that several employees' performance was starting to decline. Apart from that, there are differences in communication patterns that occur among employees and some organizational cultures are starting to disappear. The population in the study was 303 partners. The sample that will be used in this research is 115 respondents. The method used is Stratified Random Sampling. This research uses data collection techniques in the form of direct questionnaires. The method used in this research is a quantitative method with primary data sources taken from respondents' answers to statements in the questionnaire that has been distributed. The analysis method used is Multiple Linear Regression Analysis with IBM SPSS 25 as the analysis tool. The research results show that motivation has a significant effect on employee performance, organizational culture has a significant effect on employee performance, leadership has a significant effect on employee performance, and communication can strengthen the influence of motivation, organizational culture and leadership on partner performance at PT Kangzen Kenko Indonesia Jember Branch. This research can be used as a reference for PT Kangzen Kenko Indonesia Branch in conducting evaluations to improve partner performance, especially in the marketing department. Keywords: motivation, organizational culture, leadership, communication and partner performance. 1. P